Evolution Du Couvert Végétal Naturel Au Niveau Des Massifs Forestiers De Mallalyine Et Taghramt (Rif Occidental Du Maroc) - Houssni, Mhammad; Ennouni, Hassan; Ouallali, Abdessalam; Kassout, Jalal; El Mahroussi, Mohamed; Sahli, Abdelouahab; Bensbih, Hasnae; Kadiri, Mohamed; Ater, Mohammed (European Scientific Journal, ESJ, 2018)
This work presents the results of a cartographic study of the spatiotemporal evolution of vegetation cover in the forest areas of Mallalyine and Taghramt in the western Rif. It is based on a field survey and the photointerpretation of aerial photographs taken in 1986 and Google Earth images from 2013 (a period of twenty-seven years). Our study reports on the current state of degradation of the vegetation cover in the forests of Mallalyine and Taghramt. We have produced two land use maps showing how high and low formations as well as scrub have regressed by 62, 70 and 49 percent, respectively, between 1986 and 2013, while non-forested land and reforestation increased respectively by 26.3 and 1.53 percent relative to the area covered in 1986. The main factors contributing to the decline of vegetation cover are: deforestation (35 offenses registered every year with a degraded area of about 15 ha / year), clearing (27 offenses per year with an European Scientific Journal August 2018 edition Vol.14, No.24 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 20 affected area of about 20 ha / year), overgrazing (10 offenses of illegal grazing per year with a degraded area of about 12 ha / year), forest fires (4 to 5 fires per year with a degraded area of about 50 ha / year). In addition to these factors, we find increasing water scarcity.